PARADOKS DIGITALISASI PELAYANAN PUBLIK: STUDI KESENJANGAN DESAIN-REALITAS DAN PERSISTENSI BIROKRASI MANUAL DALAM IMPLEMENTASI M-PASPOR - Nur Muhammad Alil Makmur S; Herman H; Muhammad Irvan Nur I’va; Rahayu Rahayu; Andi Asrifan (Jurnal Progress Administrasi Publik, 2026)
Digital transformation is not simply a conversion from manual to electronic, but rather a fundamental shift in how organizations create public value. In the context of M-Passport, system failures are often caused not by programming weaknesses alone, but by the unpreparedness of the surrounding ecosystem. Data shows that despite the application's launch in January 2022, many Technical Implementation Units (UPTs), such as in Makassar, still implement hybrid practices where physical documents remain the "primary source of truth" over digital data. This study aims to analyze the barriers to implementing the M-Paspor application innovation at the Class I Immigration Office of Makassar. The research employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation involving immigration officers and application users. The results indicate that the main obstacles lie in technical aspects (system and network disruptions), human resources (limited digital literacy among staff and citizens), and managerial issues (lack of evaluation and coordination between agencies). Based on Mulgan and Albury’s (2003) innovation theory and the e-governance implementation barriers framework, these challenges arise from low organizational readiness and weak adaptation to innovation. This study recommends improving human resource capacity, optimizing technological infrastructure, and strengthening digital literacy in society. The findings contribute to the development of digital-based public innovation management strategies in immigration services.   Keywords: E-Governance; Immigration; M-Paspor; Public Innovation; Public Service